Hereditary leukoencephalopathy with axonal spheroids: a spectrum of phenotypes from CNS vasculitis to parkinsonism in an adult onset leukodystrophy series. Issue 5 (2nd May 2015) - Lynch, David S; Jaunmuktane, Zane; Sheerin, Una-Marie; Phadke, Rahul; Brandner, Sebastian; Milonas, Ionnis; Dean, Andrew; Bajaj, Nin; McNicholas, Nuala; Costello, Daniel; Cronin, Simon; McGuigan, Chris; et al.
Abstract : Background: Hereditary diffuse leukoencephalopathy with neuroaxonal spheroids (HDLS) is a hereditary, adult onset leukodystrophy which is characterised by the presence of axonal loss, axonal spheroids and variably present pigmented macrophages on pathological examination. It most frequently presents in adulthood with dementia and personality change. HDLS has recently been found to be caused by mutations in the colony stimulating factor-1 receptor ( CSF1R ) gene. Methods: In this study, we sequenced the CSF1R gene in a cohort of 48 patients from the UK, Greece and Ireland with adult onset leukodystrophy of unknown cause. Results: Five pathogenic mutations were found, including three novel mutations. The presentations ranged from suspected central nervous system (CNS) vasculitis to extrapyramidal to cognitive phenotypes. The case histories and imaging are presented here, in addition to neuropathological findings from two cases with novel mutations. Conclusion: We estimate that CSF1R mutations account for 10% of idiopathic adult onset leukodystrophies and that genetic testing for CSF1R mutations is essential in adult patients presenting with undefined CNS vasculitis or a leukodystrophy with prominent neuropsychiatric signs or dementia.